'Facing it Together': Early Caregiving Responses to Vancouver's HIV/AIDS Epidemic. Issue 3 (16th August 2021) - Klassen, Benjamin
Abstract: This article utilises oral history interviews with long‐term survivors and caregivers in Vancouver, British Columbia to foreground the importance of gay men's early HIV/AIDS caregiving work. Caregiving was essential to the health and resilience of Vancouver's gay community and served as a political response to homophobic discourses that demonised gay men and devalued the lives of people living with HIV/AIDS. This analysis of the practical and political significance of HIV/AIDS caregiving demonstrates that historians must find better ways to recover the often‐untold histories of men's caregiving and domesticity and appreciate their significance to the success of social movements.